The efficiency of public expenditure on Higher Education: a study with Brazilian Federal Universities - David Daniel Hammes (Ensaio: Avaliação e Políticas Públicas em Educação, 2020)
This study aims to describe the determining factors in efficiency of public expenditures in Brazilian Federal Universities. A two-stage survey method was applied for a sample of fifty-nine Brazilian Federal Universities, from 2013 to 2017. The Data Envelopment Analysis (DEA) was applied for the first stage in order to measure the efficiency of public expenditures. For the second stage, a truncated regression model was applied, with a double bootstrap procedure for bias correction and statistical significance test of the variables. Results show that some Brazilian Federal Universities were inefficient during this period. Considering the truncated regression model of Simar and Wilson (2007), significant variables that influence the efficiency of public expenditures in federal universities were: public expenditures in Higher Education, number of professors, amount of enrolments, amount of graduates, total expenditures with employees and total amount of employees. Therefore, this study has contributed to scientific literature showing that these variables play a key role to public efficiency in federal universities.